2013
DOI: 10.5812/traumamon.5094
|View full text |Cite
|
Sign up to set email alerts
|

Application of Removable Wrist Splint in the Management of Distal Forearm Torus Fractures

Abstract: BackgroundThere is considerable variation in the treatment of distal forearm torus fractures (DFTF), from soft bandaging to cast immobilization.ObjectivesThe present study aimed to show the result of removable wrist splint (RWS) in the treatment of these fractures.Materials and MethodsOne hundred forty two children aged less than 17 years old with DFTF were studied prospectively. These patients were randomly treated either by a short arm cast (SAC) or a RWS for three weeks. Finally the treatment results of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Of further concern, the utilization of radiographic and clinical follow-up, the duration of follow-up and the prescribed duration of immobilization were greater than the recent evidence suggests is necessary for safe management. 2 , 6 , 9 , 10 , 17 , 18 Additionally, when comparing the early and late groups to evaluate for changes in practice patterns over the study period, we identified no statistically significant differences in the metrics studied. Together, these results suggest the enduring tendency to over-treat this injury.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Of further concern, the utilization of radiographic and clinical follow-up, the duration of follow-up and the prescribed duration of immobilization were greater than the recent evidence suggests is necessary for safe management. 2 , 6 , 9 , 10 , 17 , 18 Additionally, when comparing the early and late groups to evaluate for changes in practice patterns over the study period, we identified no statistically significant differences in the metrics studied. Together, these results suggest the enduring tendency to over-treat this injury.…”
Section: Discussionmentioning
confidence: 82%
“…The benefits of splinting have been seen in regards to function, hygiene, cost, convenience and patient and caregiver satisfaction without increased risk of treatment failure. 2 , 6 , 9 , 10 , 17 , 18 Furthermore, although we opted to exclude non-torus fractures of the wrist (i.e. greenstick and transverse) from the current study, a 2010 randomized controlled trial by Boutis et al 19 suggests that these injuries may also be safely managed with a removable device for four weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Within Category C effect sizes were calculated for one study [ 84 ] and odds ratios for three studies [ 79 – 81 ]. O’Connor et al [ 84 ] compared a plaster cast to a wrist splint for a Colles’ fracture with no differences in participant satisfaction or pain evident between the groups.…”
Section: Resultsmentioning
confidence: 99%
“…Harding et al [ 80 ] compared a metacarpal brace to neighbour strapping with the brace group more likely to return to work within 3 weeks (OR: 0.04 (0.01 to 0.15)) and more satisfied with the intervention (OR: 0.80 (0.26 to 2.44)). Karimi Mobarakeh et al [ 81 ] compared a plaster cast to a wrist splint with the splint more beneficial in terms of convenience (OR: 0.72 (95% CI 0.26 to 1.99)), but the plaster cast was more beneficial in relieving pain (OR: 1.59 (0.79 to 3.18)).…”
Section: Resultsmentioning
confidence: 99%
“…Karimi et al in his study has shown good results in torus fractures in patients less than 17 years of age using removable wrist splint. He, however, studied only the patients of less than 17 ( 16 ).Bahari-Kashani et al (2003) studied the intra-articular distal end radius fractures managed by pin and plaster or plating. They concluded that functional scoring, radiological indices, grip strength, and supination pronation were better in the plating group ( 17 ).…”
Section: Discussionmentioning
confidence: 99%